Pengaruh Dampak Dari Model Kepemimpinan Terhadap Motivasi Kerja Karyawan Pada PT. Multi Garmen Jaya (Cardinal) - Dani, Dani Sulaeman; Amilia Tresnawati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
This research aims to find out the impact of the leadership model on employee work motivation at PT. Multi Garment Jaya. Data analysis in this study used a normality test using the Kolmogorov-Smirnov method and simple linear regression with calculations assisted by the SPSS program. The results of the research and discussion obtained a significance value of 0.000, which is smaller than the significance level of 0.05. Then the value of tcount (4.126) > ttable (2.011). This shows that there is an influence of the leadership model on employee work motivation at PT. Multi Garmen Jaya or in other words Ha is accepted. The influence of leadership models on employee work motivation. Keywords: Leadership Style, Work Motivation